Optimasi keuntungan dengan metode Branch and Bound - Sri Siti Supatimah; Farida Farida; Siska Andriani (Universitas PGRI Semarang, 2019)
Sentral Me Laundry is one of the service services businesses established in 2016 and has 2 employees having their address at Jalan pulau Ambon, Sukarame, Bandar Lampung. The development of laundry services in the middle of the city community indicates that laundry businesses can still develop and can achieve optimal profits. The purpose of this study was to find the optimal benefits obtained by the Sentral Me Laundry business. Errors in planning a laundry business result in a maximum profit. To prevent mistakes in planning a laundry business, it is necessary to use the right method. Banch And Bound Method (Integer Linear Programming) is a method that can be used to optimize laundry business by looking at the limited resources of the business. In the linear program method the decision variable can be a real number. While the optimization of laundry business that will be done requires a solution in the form of an integer called Integer. To help resolve cases of optimizing the benefits of laundry businesses using a computer program, QM For Windows. Calculations from the QM For Windows program produce 53 Kg of Badcover, 188 Kg of Doll, 1350 Kg of Clothing, 101 Kg of Blanket.. Keywords: Branch and Bound; Optimization; QM For Windows